Qualitative Analysis of Curriculum Components Aligned with Education for Sustainable Development (ESD) - Baghaei, Hossein; Valizad Ziyaei , Parisa; Valipour, Fatemeh; Gassabi Kaleybari, Raha; Asgharzadeh, Parvin (Assessment and Practice in Educational Sciences, 2025)
The objective of this study was to qualitatively analyze the curriculum components aligned with Education for Sustainable Development (ESD) within the Iranian educational context. This study employed a qualitative research design with an interpretive approach to explore philosophical, pedagogical, structural, and institutional dimensions of ESD-based curriculum development. The participants consisted of 22 curriculum experts, teachers, and educational administrators from Tehran, selected through purposive sampling until theoretical saturation was achieved. Data were collected through semi-structured interviews lasting between 45 and 75 minutes and analyzed thematically using NVivo 14 software. Thematic coding involved open, axial, and selective stages, ensuring the identification of core categories and subthemes. Trustworthiness was established through member checking, peer debriefing, and audit trail procedures, and ethical approval was obtained from the Islamic Azad University, South Tehran Branch. The analysis revealed four major themes: (1) Curriculum philosophy and vision, emphasizing moral, ethical, and cultural contextualization of sustainability; (2) Pedagogical approaches and teaching strategies, highlighting experiential, participatory, and technology-enhanced learning; (3) Curriculum content and structure, focusing on interdisciplinary integration, policy alignment, and inclusion of environmental and socio-economic dimensions; and (4) Teacher capacity and institutional support, underlining the importance of professional development, institutional culture, and leadership commitment to ESD. Participants’ narratives illustrated that effective ESD implementation requires coherence among curriculum philosophy, pedagogy, and governance mechanisms. The study concludes that achieving Education for Sustainable Development in Iran necessitates a transformative approach to curriculum design, integrating ethical foundations, innovative pedagogies, and systemic institutional support. Embedding sustainability principles within all educational levels can foster critical thinking, moral responsibility, and collective action toward sustainable futures.